BRINCANDO DE APRENDER: UM RECURSO PARADIDÁTICO PARA A APRENDIZAGEM DE CIÊNCIAS NA EDUCAÇÃO INFANTIL - Vieira, Maria Lucia Silveira (2023)
This study is part of the line of research Teaching and Learning in Science and Mathematics, of the Postgraduate Program in Science and Mathematics Teaching at the Franciscan University and arose from concerns about learning gaps arising from the period of the covid pandemic. - 19, which lasted from 2020 to 2021. In Early Childhood Education, according to the National Common Curricular Base (BNCC), learning and development are linked to the six rights: Living, Playing, Participating, Exploring, Expressing and Knowing yourself. In the context of the pandemic, with remote classes or the delivery of physical material for children to use, school coexistence became difficult. In this research, the five fields of experience of the BNCC are also taken into account. Based on this concern, the following research problem was defined: what are the possible contributions of a paradidactic resource to recover science learning in Early Childhood Education, considering the weaknesses of teaching during the pandemic? With this, the general objective was to analyze the possible contributions of a paradidactic resource to recover science learning in Early Childhood Education, considering the weaknesses of teaching during the pandemic. The study is structured as follows: introduction; theoretical basis, methodological aspects, results and discussion and final considerations. The educational product consists of a paradidactic magazine, aimed at children, aged between 1 year and 7 months to 3 years and 11 months. It was applied to a class of 20 students, from a municipal school in the city of Santa Maria (RS). It was found that the children demonstrated enthusiasm and joy in carrying out the activities, through imagination they reported their reading of each drawing, they explored the world of colors through painting, they used their creativity to color, trace and cut, they exchanged ideas while handling the magazine.